Mediating Role of Mindfulness Between Loneliness and Relationship Quality in Married Couples Dyadic Approach - Korun, Ali Berke; Satici, Seydi Ahmet; Erdinc, Beste; Akyil, Yusuf (SAGE PUBLICATIONS INC, 2026)
The predominant subject of current research is the influence of couples with maladaptive interaction patterns on one another. The research examined the relationships among the concepts of loneliness, mindfulness, and relationship quality. Specifically, it elucidates the dynamics between couples. This study investigated the impact of spousal loneliness on the quality of relationships among 401 married couples (N = 802) utilizing a dyadic approach via an actor-partner interdependence mediation model, emphasizing mindfulness. The research demonstrated substantial actor effects among loneliness, mindfulness, and relationship quality across all genders. The analysis indicated that women's loneliness had an indirect effect on relationship quality via men's mindfulness. The partner effect indicates that women's loneliness may diminish their male partners'mindfulness, consequently impairing the quality of women's relationships. The research revealed that men's loneliness has an indirect impact on the quality of women's relationships via mindfulness. The partner effect indicates that men's loneliness may diminish their female partners'mindfulness, consequently lowering men's relationship quality. All findings are examined and elucidated in alignment with the current literature.
Keywords: loneliness; mindfulness; relationship quality; actor-partner interdependence mediation model; ROMANTIC RELATIONSHIPS; LIFE SATISFACTION; MENTAL-HEALTH; ASSOCIATIONS; IMPACT; YOUNG; Family Studies